Implementasi Pembelajaran Coding Berbasis Scratch Sebagai Upaya Inovasi Pembelajaran Informatika di SMP Al Islam - Bayu Dwi Raharja; Didik Nugroho; Rahmatika Rahmatika (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
The development of digital technology forces educational institutions to implement informatics learning that focuses not only on the use of tools, but also on improving computational thinking and problem-solving skills. However, informatics learning in junior high schools still faces problems, such as limitations in interactive learning materials and low student enthusiasm for programming lessons. This community service activity aims to implement coding learning using Scratch as part of an innovative effort in teaching informatics at Al Islam Junior High School. The method used is mentoring and practice-based training with a project-based learning approach. The participants were eighth-grade students from Al Islam Junior High School who were actively involved in creating animations and simple games using Scratch. The results of the activity showed that students' understanding of basic programming concepts, such as logic, command sequences, repetition, and branching, had increased. In addition, students' interest and participation in learning informatics also increased. This activity has a positive impact on the quality of informatics learning and can be an example of digital learning innovation at the junior high school level.